Effect of Integrated Nutrient Management on Yield, Nutrient Uptake, Protein Content, Soil Fertility and Economic Performance of Rice (Oryza sativa L.) in a Vertisol - Narendra Chouhan and K.S. Keram, G.D. Sharma, Risikesh Thakur (Journal of the Indian Society of Soil Science, 2015)
A field experiment was conducted during 2010 and 2011 to assess the effect of combined application of fertilizer, organic manures and biofertilizers on yield, nutrient utilization along with soil fertility in rice. The results revealed that the substitution of 25% NPK through farmyard manure (FYM) in recommended dose of NPK along with 5 kg Zn ha-1 and PSB+BGA recorded significantly higher grain yield (3.96 t ha-1) over the 100% NPK treatment (3.49 t ha-1). Maximum nutrients uptake (N, P, K, S and Zn) by rice 75.6, 18.4, 120.1, 27.8 kg ha-1 and 231.9 g ha-1, respectively were observed in the treatment receiving 75% NPK+5 t FYM ha-1+PSB+BGA+Zn. The conjunctive use of organic manure and fertilizers along with biofertilizers and micronutrients gave highest availability of N, P, K, S and Zn at post-harvest soil of rice as compared to other treatment combinations. The B:C ratio computed for rice suggested that the higher B:C ratio is associated with higher production and better quality of the produce and therefore more economical. Thus, integrated resource management improved the crop yields, produce quality grain as well as improved the soil fertility, thus the overall profit of the farmers. Integrated nutrient applications are more beneficial when the rate of nutrient application is below the normal rate.